2018
DOI: 10.3766/jaaa.17059
|View full text |Cite
|
Sign up to set email alerts
|

Inter-regional Newborn Hearing Screening via Telehealth in Ghana

Abstract: Background: Newborn hearing screening is a vital aspect of the Early Hearing Detection and Intervention program, aimed at detecting hearing loss in children for prompt treatment. In Ghana, this kind of pediatric hearing service is available at only one health care facility located in the Greater Accra Region. The current practice in effect has virtually cut-off infants in the other regions from accessing hearing screening and other pediatric audiological services. This has prompted a study into alternative met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Over the last decade, Tele-audiology (including remote HL) has grown significantly as the technological landscape has altered [43] . Ameyaw et al reported that using distortion product otoacoustic emissions to screen newborn hearing over the Internet was comparable to the traditional face-to-face on-site HS approach [44] . The ongoing omicron pandemic has had a tremendous impact on society because of its incredible spread and intrinsic severity [45] .…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, Tele-audiology (including remote HL) has grown significantly as the technological landscape has altered [43] . Ameyaw et al reported that using distortion product otoacoustic emissions to screen newborn hearing over the Internet was comparable to the traditional face-to-face on-site HS approach [44] . The ongoing omicron pandemic has had a tremendous impact on society because of its incredible spread and intrinsic severity [45] .…”
Section: Discussionmentioning
confidence: 99%
“…Both the study by du Plessis et al and Ameyaw et al [ 52 , 67 ] focused on the detection and diagnosis of deafness or hearing loss. The first study involved the establishment of an interregional network with the ultimate aim of conducting a comparative analysis between two hearing screening techniques, carrying it out remotely and face to face.…”
Section: Resultsmentioning
confidence: 99%
“…Along the same lines, studies more focused on early detection have implemented this technology to collect information based on developmental milestones or standard values of typical development. Thus, in the case of detecting any kind of deviation, this entails notifying the primary caregiver [ 50 , 53 , 67 ] and suggesting that they request an appointment with their referral center [ 50 , 53 ], enabling them to address it early.…”
Section: Discussionmentioning
confidence: 99%
“…Monica et al ( 57 ) conducted remote synchronous audiometric and DPOAE screenings in school-aged children ( n = 31) in India using teachers as facilitators and found results similar to traditional, in-person testing. Ameyaw et al ( 58 ) examined remote synchronous DPOAE screenings in a group of newborn infants ( n = 50) in Ghana. Screenings were completed in-person and remotely by an audiologist via the internet with real-time audio, video, and text messaging between the facilitator and audiologist.…”
Section: Tele-audiology Servicesmentioning
confidence: 99%